Development of a PCR method to detect polymorphism of angiotensin converting enzyme / Nurul Fazleen Abdul Malik - Abdul Malik, Nurul Fazleen (2013)
Angiotensin converting enzyme (ACE) is an enzyme responsible for the conversion of angiotensin I to angiotensin II and degradation of bradykinin. Polymorphism of ACE means that there is variation in the nucleotide sequence of ACE gene due to insertion (I) or deletion (D). There are several types of polymorphism of ACE, in which it may give different responses whether by enhancing or reducing the efficiency of ACE inhibitor. The aim of this study is to develop a PCR method to detect polymorphism of ACE gene. The primer were designed according to the gene and followed by reconstitution of primer working stock. DNA sensitivity was performed in order to detect the lowest concentration of DNA template that can be used for PCR method. Besides that, different DNA of patient was used in order to detect polymorphism of ACE by using this PCR method. Based on the result of this study, it can be concluded that VD polymorphism of ACE gene was not successfully amplified by using the PCR. It is suggested that for next studies to used Restriction Fragment Length Polymorphism (RFLP) method for more accurate results.